INVESTIGATING FATIGUE PERFORMANCE ON THE FOAMED ASPHALT SPECIMENS GENERATED USING DIFFERENT FOAM PROPERTIES - Sunarjono, Sri (Jurnal Transportasi, 2012)
An evaluation of fatigue resistance for foamed asphalt mixture is very demanding since the binder is not continuously distributed on the aggregate surface and this mixtures contains water, the content of which dramatically affects the mechanical properties. This paper discusses the results of laboratory fatigue testingon the foamed asphalt mixtures in which the specimens are generated using three different foamed bitumen properties. Foamed bitumen as the binder was produced at three different foaming water content (FWC) at a temperature of 180oC using a 70/100 pen. The aggregates were mechanically mixed with foamed bitumen using a Hobart mixer. The resulting mixtures were then compacted using a gyratory compactor to generatespecimen with diameter of 100 mm. The specimens were fatigue tested at various stress levels at a temperature of 20oC following a curing period of 3 days at 40oC. Overall, fatigue performance of foamed asphalt can be identified based upon both stress and strain for mixtures produced at FWC 1%, 5%, and 10%.Keywords: fatigue performance, foamed asphalt, binder, foaming water content.